The effects of formic acid or herbal mixture on growth performance, carcass quality, blood chemistry, and gut microbial load in broiler chickens - Mohamed E. Abd El-Hack; Ahmed K. Aldhalmi; Elwy A. Ashour; Mahmoud Kamal; Mohammad M.H. Khan; Ayman A. Swelum (Poultry Science)
The purpose of this research was to assess the effects of formic acid (FORM) and an herbal mixture (HM) as antibiotic alternatives in broiler meals on growth efficiency, carcass criteria, blood parameters, and intestinal bacterial populations. A total of 360 one-day-old Ross 308 broiler chicks were assigned to six trial treatments using a totally randomized method. Each group consisted of 6 replicates, with 10 unsexed chicks per replicate. The groups were arranged as follows: NC (negative control, basal diet); PC (positive control, basal diet + 0.5 g Polymyxin E antibiotic/kg diet); Form2, Form4, HM3, and HM6 (basal diet supplemented with 2 or 4 ml formic acid, or 3 or 6 g herbal mixture/kg diet, respectively). The findings showed no substantial variations in ''body weight (BW) or body weight gain (BWG)'' among the formic acid and herbal mixture groups relative to the NC and PC groups. The HM 3 and 6 g/kg groups exhibited higher ''feed intake (FI) and improved feed conversion ratio (FCR)'' relative to the other treatments. Carcass characteristics were not substantially impacted by formic acid or herbal mixture supplementation, except for spleen weight, which was highest in the NC group. Significant changes in blood parameters were observed, with notable variations in ALT and AST activity and ''urea, creatinine, total protein, globulin, and albumin'' levels in the formic acid and herbal mixture groups. The supplementation of formic acid and herbal mixture also increased antioxidant levels (GPx, GST, and GSH) compared to the NC group while reducing MDA levels relative to the NC and PC groups. Additionally, formic acid supplementation significantly reduced harmful bacterial populations in cecal samples. Conversely, Lactobacilli counts greater than those in the NC and PC groups, although no significant variances in Clostridium populations were observed. In conclusion, supplementing broiler feed with formic acid and herbal mixtures positively influences blood parameters, antioxidant status, and intestinal microbiota.